Research on the Development Status, Problems and Suggestions of the STAR Market - Wei, Xiangmeng (Transactions on Economics, Business and Management Research, 2024)
In 2018, the STAR Market was newly established on the Shanghai Stock Exchange and piloted the registration system. Since then, science and technology enterprises have been revitalized and energized in the STAR Market. In July 2023, the STAR Market ushered in the fourth anniversary of the market's opening. In the past four years, the STAR Market has operated steadily and made remarkable achievements. In October 2023, the Central Financial Work Conference pointed out that it puts science and technology finance first and that efforts should be made to build a financial power. This paper explores the current situation and problems of the development of the STAR Market from four perspectives: market issuance, market activity, market profitability, and market innovativeness, and puts forward corresponding countermeasures and suggestions to further play an essential role in promoting the development of science and technology finance in China.